New Trajectory of Kyai’s Political Participation in Contemporary Indonesia: Rises, Challenges, and Opportunities - Chalik, Abdul; Hamdi, Ahmad Zainul (Indonesian Journal of Political Studies, 2022)
The political roles of Kyai post-1998 political Reformation has always been an interesting theme to be debated. This article discusses the rise, the challenges, and the various opportunities which open the new direction for kyai’s political participation in Indonesia post-political Reformation. This article uses the political and social science approaches on qualitative data and literature review regarding kyai’s political history in Indonesia. The results show that the openness of the post-Reformation politics opens doors for the kyai to enter electoral politics by using religious authorities (traditional and charismatic authorities in the Weberian perspective) also the extensive support network which follows the pesantren (Islamic boarding school) network, alumni, and tarekat. Kyai’s entrance in the post-Reformation electoral politics have opened a new era in Indonesia’s political history. A new generation of pesantren figures with good competences in the political views is born. The kyai’s participation is basically a transformation from the subject culture to the participant culture